Discourse particles in Kurmanjî Kurdish-Turkish contact. Issue 4 (1st October 2020) - Çabuk, Sakine
ABSTRACT: Exploring interaction among Kurdish speaking family members, this paper investigates the use of discourse particles in Kurmanjî-Kurdish in relation to the contact phenomenon between the Kurdish and Turkish languages. Corpus analysis of data obtained from audio and video recordings of family talk on the phone was carried out to examine semantic-pragmatic properties of discourse particles. Although some particles in the corpus seem to be unique to Kurdish, some others appear to be borrowed from Turkish and integrated into Kurdish by undergoing some phonological changes. The findings suggest that Kurdish speakers borrow some lexical items and integrate them into Kurdish with some changes at phonological level or combine them with some Kurdish particles. Even though Kurdish and Turkish languages have close contact and long-lasting coexistence in the linguistic setting of Turkey, which results in borrowing of some particles from Turkish and their use in daily interaction by Kurdish speakers, it is hard to reach a conclusion about language change at this level. Abbreviations: ADP: Adposition; COP: Copula; DAT: Dative; DP: Discourse Particle; IZF: Izafe; NEG: Negation; OBL: Oblique Case; 1SG: First person singular; OPT. FUT: Optative Future; 2SG: Second person singular; OPT.PRS: Optative Present; 3SG: Third Person singular; PRS: Present; 1PL: First person plural; PROG: Progressive; 2PL: Second person plural; PST: Past; 3PL: Third person plural